Quick Determination of Electroactive Surface Area of Some Oxide Electrode Materials. Issue 10 (6th October 2016) - Watzele, Sebastian; Bandarenka, Aliaksandr S.
Abstract: Quick and accurate determination of the real electroactive surface area of oxide electrodes remains one of the most challenging but at the same time important unsolved methodological tasks in the field of electroanalysis. For instance, the widely used Brunauer−Emmett−Teller (BET) method unfortunately provides no direct connection to it. On the other hand, its assessment through the double layer capacitance is complicated and not accurate enough, as the bulk oxide films themselves contribute to the measured capacitance, not mentioning the double layer frequency dispersion and other poorly understood factors. In this work, we propose a relatively simple methodology for a quick assessment of the electroactive surface area of some electron conducting oxide and perovskite materials. The methodology involves several steps. Initially, "calibration" experiments are performed aiming to form the thinnest (practically below ∼100–200 nm) flat oxide films, which exhibit necessary functional properties (close to those expected for the bulk material) without significant side influence of the substrate. Then, AFM measurements are implemented to estimate the surface roughness of the resulting samples. Finally, electrochemical impedance measurements are done at a small overpotential related to the oxygen evolution reaction (OER) aiming to extract not the double layer but the capacitance of adsorption C a of the OER intermediates. The C a values can then be used to evaluate the electroactive surface area of "real‐world" high surface area oxide electrodes composed of the same material. Other words, similar to the hydrogen underpotential deposition or CO oxidation in the case of metals, we propose to use the oxygen evolution reaction as the probing reaction to evaluate the surface area of oxide electrocatalysts. However, instead of cyclic voltammetry, electrochemical impedance spectroscopy is used as the main probing technique. Due to relatively high reproducibility, clear physical meaning and exclusive connection to the electroactive area, the measurements of C a can become a viable method in numerous electrochemical applications. An example using Ni‐oxide electrodes is given to illustrate the methodology. Abstract :